Lactobacillus plantarum GMNL-662 and Lactobacillus plantarum 299v prevent osteoporosis in mice with colitis by down-regulating Akkermansia in the gut microbiome. (December 2022) - Xu, Yuhan; Xie, Qiaoling; Zhang, Wei; Zhu, Meizhen; Chen, Xiaoxuan; Guo, Dongbei; Pan, Lili; Li, Junru; Lan, Hui; Li, Hongwei
Graphical abstract: In Brief: Lactobacillus plantarum GMNL-662 (Lp662) and Lactobacillus plantarum 299v (Lp299v) intervention have a protective effect on osteoporosis caused by colitis induced by DSS, partially through changes in the gut microbiota and a decrease in inflammatory factors. Highlights: This study assessed the effects of probiotics on severe inflammatory bowel disease and osteoporosis. DSS-induced colitis was used to induce osteoporosis, and short-term (21 days) intervention of probiotics Lactobacillus plantarum GMNL-662 and Lactobacillus plantarum 299v were used to explore its protective effects. Explore the relationship between intestinal inflammation, gut microbiota, and osteoporosis. Probiotics' therapeutic potential as an anti-inflammatory treatment to reduce bone loss was suggested. Abstract: The effects of probiotics Lactobacillus plantarum GMNL-662 (Lp662) and Lactobacillus plantarum 299v (Lp299v) treatment on severe inflammatory bowel disease induced by dextran sodium sulfate was assessed. Male C57BL/6J mice (6 weeks old) were administered 0.9% NaCl, Lp662, or Lp299v by gavage during the entire experiment. After 3 weeks, gut inflammation was associated with bone loss, and compared to the control group, the weight loss caused by colitis in the Lp662 and Lp299v groups decreased ( P < 0.001). Pathological sections of the colon showed that probiotics reduced tissue injury, and serum and tissue inflammatory factors decreased significantly ( P < 0.05) compared to the control group. Three-dimensional reconstruction images showed that the bone mass in the Lp662 and Lp299v groups was significantly higher than that in the control group. This study highlights the negative impact of chronic gut inflammation on the bone and the therapeutic potential of probiotics as an anti-inflammatory treatment.